Scientific and technological activities of TNC: current trends and prospects (Economics and region, 2020)
In the article the authors consider the features of scientific and technological activities of transnational corporations, highlight the main trends and prospects for its development. In particular, it is emphasized that the source of modern development of society and human activity is innovation, and accordingly innovation becomes an important tool for all radical changes in human development and the economic system in general. Scientific and technological development of transnational corporations is a crucial prerequisite for ensuring their profitable activities. The purpose of the article is to analyze current trends and prospects for the development of scientific and technological activities of transnational corporations. The article examines the features of the R & D organization in multinational corporations. The dynamics of expenditures in individual leading TNCs on R&D is given. It is noted that the global nature of competition not only makes innovations more significant for TNCs, but also necessitates the search for new ways to innovate. The paper identifies the main types of technological policy, identifies the reasons for the centralization and decentralization of R & D, as well as possible risks that arise in the implementation of these policies. The experience of developed countries shows that competitiveness is ensured by a number of conditions, the main of which are the accumulated scientific and technological potential, institutional factors of technological progress and the presence of large knowledge-intensive corporations. Therefore, the current trend of scientific and technological activities of TNCs is a new wave of mergers and acquisitions (M&A). The authors present the largest mergers and acquisitions at the beginning of the XXI century. In the last two decades, as a result of the growing internationalization of research, the trend of forming strategic alliances has sharply increased, especially due to the merger of companies in such high-tech industries as pharmaceuticals, telecommunications, semiconductors, etc. Special attention is paid to analysis of the reasons for the formation of strategic alliances. It is shown that in some cases competitors become partners in strategic alliances in high-tech industries. In conclusion, it is noted that in conditions of fierce competition in both international and domestic markets, the ability of companies to operate and develop depends on their ability to create and implement innovations. It is innovations that cause continuous economic change, contribute to the dynamic development and increase the efficiency of both the economic system as a whole and individual enterprise. The scientific and technological development of corporations is the main prerequisite for ensuring and increasing their international competitiveness.
Keywords: scientific and technological activity; transnational corporations; international competition; innovations; technological policy